Legal Protection of Traditional Crafts Tapis Lampung Based Local Wisdom in The Era of Globalization - Erlina B (International Conference On Law, Business and Governance (ICon-LBG), 2013)
New technologies that arise from globalization without pushing the limits of local cultural renewal effort that his form can be imitation, exchange, use new or refurbished, then removes the values contained in the local cultural products. It affects the traditional culture of creativity itself. The challenge for Indonesia is a need for policies that are able to manage the balance between protection, maintenance, and development of handicrafts diversity as cultural heritage. It thus applies to other communities that have similar cultural diversity with Indonesia. There should also be a free atmosphere in the spirit of openness that meeting and exchange of cultural experiences between local and migrant communities will enrich the cultural diversity.Legal protection of traditional crafts lampung filter based on local wisdom in the era of globalization is a form of legal development in the regional economy, this is done because the traditional craft Lampung filter turns out that ideally should be protected by laws and regulations lack legal protection, but this craft is heritage values have philosophical, spiritual, cultural. Crafting legal protection filter needs to be done in the form of Lampung legal development based on local wisdom, this is done so that the spirit of the values underlying the legal protection capable of blending in the heart Lampung. Fore, this legal protection implies a return of function cloth filter for Lampung society as sacred objects that have symbolic meaning associated with the philosophical and religious beliefs become commodity products trading intelligently.